2022
DOI: 10.1001/jama.2021.23732
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Atrial Fibrillation

Abstract: ImportanceAtrial fibrillation (AF) is the most common cardiac arrhythmia. The prevalence of AF increases with age, from less than 0.2% in adults younger than 55 years to about 10% in those 85 years or older, with a higher prevalence in men than in women. It is uncertain whether the prevalence of AF differs by race and ethnicity. Atrial fibrillation is a major risk factor for ischemic stroke and is associated with a substantial increase in the risk of stroke. Approximately 20% of patients who have a stroke asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The US Preventive Services Task Force has concluded that evidence for screening for AF in individuals ≥50 years of age remains lacking. 143…”
Section: Disorders Of Heart Rhythmmentioning
confidence: 99%
See 1 more Smart Citation
“…The US Preventive Services Task Force has concluded that evidence for screening for AF in individuals ≥50 years of age remains lacking. 143…”
Section: Disorders Of Heart Rhythmmentioning
confidence: 99%
“…142 The US Preventive Services Task Force has concluded that evidence for screening for AF in individuals ≥50 years of age remains lacking. 143 A systematic review of 19 studies from 2007 to 2018 identified 24 single-time-point screening studies; 141 220 participants were included, of whom 1539 had newly detected AF. The detection rate adjusted for age and sex was 1.44% (95% CI, 1.13%–1.82%) in those ≥65 years of age and 0.41% in individuals <65 years of age.…”
Section: Disorders Of Heart Rhythmmentioning
confidence: 99%
“…Current European guidelines recommend systematic electrocardiogram screening to be considered in individuals aged ≥75 years or at high stroke risk [6], while the most recent US Preventive Services Task Force Recommendation Statement states a lack of sufficient evidence to endorse AF screening [34]. However, this post hoc analysis of the LOOP Study demonstrates that the effects of systematic AF screening on stroke prevention was considerably upheld by high-risk individuals without established CVD.…”
Section: Tablementioning
confidence: 91%
“…Recently, the United States Preventive Services Task Force (USPSTF) 88 published the 2022 updated version of their document dedicated to AF screening, still highlighting their concern about the lack of effectiveness of an AF screening structured pathway as compared to usual care opposed to some risk of adverse events, as anxiety, excessive testing, and overtreatment. Thus, given that current evidence is deemed insufficient to assess the balance of benefits and harms of screening for AF, the agency has expressed against the implementation of screening in asymptomatic adults aged ≥50 years.…”
Section: Current Guideline Recommendationsmentioning
confidence: 99%
“…Moreover, performing AF screening do not recognize clear contraindications, while some caution is needed regarding possible adverse effects such stress/anxiety or overdiagnosis/overtreatment. 88 The main point of debate is still related to their effectiveness in reducing risk of stroke and other adverse events. Despite some methodological and contextual limitations of the studies performed so far, the evidence strongly suggests that AF screening strategies are associated with a significant reduction of adverse outcomes.…”
Section: Learning Pointsmentioning
confidence: 99%